Wangari Maathai’s Environmental Bible as an African Knowledge: Eco-spirituality, Christianity, and Decolonial Thought - van Klinken, Adriaan (My University, 2022)
Recent scholarship has acknowledged the contribution of the environmental activist and Nobel Peace Prize Laureate, Wangari Maathai (1940–2011), to African ecological and decolonial thinking. As far as Maathai’s engagement with religion is concerned, scholarship emphasises her critique of Christianity for its links to colonialism and environmental degradation, and foregrounds her reclaiming of Kikuyu religion and culture as a form of indigenous African knowledge that enhances environmental awareness. However, Maathai’s simultaneous creative and constructive engagement with Christian traditions, in particular the Bible, tends to be systematically overlooked, perhaps because it seems at odds with her status as a decolonial thinker. This article examines Maathai’s engagement with the Bible, arguing that it presents an interrogation of the category of indigenous knowledge, which for her is not static but dynamic and can incorporate biblical scripture as an African knowledge. Hence, Maathai challenges scholars to take the Bible seriously as a relevant resource for environmental activism as well as for ecological and decolonial thought.
Keywords: African cultural studies; indigenous knowledge; Bible